Pengaruh Pemberian Daun Kelor dan Jantung Pisang terhadap Peningkatan Produksi Asi pada Ibu Nifas di Desa Nunkurus Kecamatan Kupang Timur Kabupaten Kupang - Filpin Luciami Ayuwandini Haning; Windy Anisa Veryany Fanggi; Oktaviana Thresia Monika Barbara Adam; Bernadeta Erni (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Childbirth is the time after labor to restore health again which takes 6-12 weeks. Giving Moringa and banana heart aims to increase the milk production. The result of a survey conducted on 15 postpartum,obtained the result of 9 people (64,28 %) experienced less milk production. The purpose of this study is to analyze the effect of Moringa leaf and banana heart on the increase of milk production in postpartum in  Nunkurus Village, East Kupang District, Kupang Regency. This research is pre experimental research. The population in this study were all postpartum in the work area of Nunkurus Village, East Kupang District, Kupang Regency.Sample size is 15 people obtained from purposive sampling technique. The result of the study were analyzed using the Wilcoxon statistical test. The result of the research showed that before the leaves were given moringa leaf and the banana heart mostly (73,3%) had milk production not smoothly and after given moringa leaf and banana heart almost whole (86,7%) experienced milk production smoothly. Based on Wilcoxon test result show data that the value of ρ = 0,003 and value a = 0,05  can be said that ρ-value <a. So H0 rejected and H1 accepted which means there is an influence of Moringa leaf and banana heart to increase milk production in postpartum mothers in Nunkurus Village, East Kupang District, Kupang Regency. It is Expected that the results of this study can provide information about the benefits of Moringa leaf and banana heart to increase milk production in postpartum in the working area of Nunkurus Village, East Kupang District, Kupang Regency.